How Cultural Alignment and the Use of Incentives Can Promote a Culture of Health: Stakeholder Perspectives - Martin, Laurie T. (Rand Health Q, 2018)
In 2013, the Robert Wood Johnson Foundation embarked on a pioneering effort to advance a Culture of Health. This report focuses on two questions that are central to understanding how individuals and sectors think about health and are motivated to promote it: How can the commonly understood concepts of cultural identity (e.g., ethnic or religious; lesbian, gay, bisexual, transgender plus; military) and organizational culture be harnessed to develop a Culture of Health? How can incentives be used to promote individual health and engage investors and leaders within organizations or governments to promote health and well-being broadly? This study draws on 43 one-hour semistructured interviews that RAND researchers conducted with stakeholders whose work focused on cultural alignment, incentives, or both to learn how organizations are addressing and leveraging culture and incentives to promote health and well-being, as well as to identify facilitators, barriers, potential best practices, and lessons learned. Key findings include the following: Equity is often addressed in silos, which impedes progress toward a unified goal of health equity for all; members of specific cultural groups need to be given a voice in health-related activities; systems are built around prevailing cultural norms, making it challenging for those working with specific cultures to make cultural adaptations; and not all incentives are monetary. Recommendations include institutionalizing practices that ensure ongoing input from marginalized populations, identifying ways to help smaller organizations overcome structural inequalities, and institutionalizing health promotion efforts in sectors other than public health or health care to sustain collaborative efforts.